THE BARRIERS AND FACILITATORS OF UNDERTAKING FLU VACCINATION IN PREGNANT WOMEN IN THE UNITED KINGDOM: A QUALITATIVE SYSTEMATIC REVIEW (Proceedings of the International Conference on Public Health, 2022)
Pregnant women are classified as one of the groups who have a high risk of flucomplications. the flu vaccination uptake in pregnant women in the United Kingdom isstill low and a slight decrease reported which was from 45.2% in 2018-2019 to 43.7% in2019-2020. This systematic review aims to explore the factors which influence pregnantwomen undertaking or refusing flu vaccination. Six electronic databases were included,such as MEDLINE, CINAHL, PsycInfo, EMBASE, PubMed, Scopus, and grey literature.This systematic review selected full texts English language and the studies from 2009 to2019. Data were assessed using CASP checklists, extracted, and synthesised. The resultsof the review are the views of pregnant women from the multicultural community frommany different countries aged 18-48 based on 4 included studies. The themes weregrouped using thematic analysis and produced 7 new analytic themes. The barriers areacceptability; service provision; lack of information; communication and interaction. Thefacilitators are benefits for the babies and the vulnerable environment. One theme thatacted as a barrier and facilitator is the influence of others, such as family, friends andcommunity. Reducing the barriers will lead to an increasing in flu vaccination uptake inpregnant women, therefore, the improvement of health care services and providing greaterinformation regarding flu vaccination are needed. The facilitators should be used as waysto inform pregnant women about the benefits and risks.
Keywords: barriers; facilitators; flu vaccination; pregnant women; United Kingdom